Analysis of The Feasibility of Sizes of Blue Swimming Crab (Portunus pelagicus Linnaeus, 1758) As Raw Materials in Processing Business Export Quality - Nurmiati, Nurmiati; Ibrahim, Muhammad Akmal; Karim, Mutemainna; Dananjaya, Wayan Kantun (Agrikan Jurnal Agribisnis Perikanan, 2023)
Blue swimming crab is one of the raw materials for fishery products which is exported to other countries so that it is suspected to have caused an increase in demand and a high intensity of fishing in nature. This study aims to analyze the feasibility of the size of the crab based on the width of the carapace and the weight of the crab as an export raw material at the processing site. The research was carried out from February to April 2023 in Bone Regency. This research is a type of qualitative research with a survey method. The results showed that the number of crabs that were successfully measured was 561 individuals with details of 292 males and 269 females with an overall carapace width size distribution ranging from 114.1 to 227.0 mm (142.74 ± 13.29 mm) and weights ranging from 103.7-863.7 g (198.48 ± 55.57g). Male carapace width 114.1-204.3 mm (141.35 ± 12.36 mm) and weight ranges from 103.7 to 633.7 g (195.38 ± 46.11g) and females with carapace width ranging from 119.0 -227.0 mm (143.16 ± 14.24 mm) and a weight ranging from 113.7 to 863.7 g (128.14 ± 64.20 g). 98.57% of the crab catches that entered the crab processing site for export raw materials met the carapace width requirements and 87.70% met the weight requirements based on the Regulations of the Minister of Maritime Affairs and Fisheries of the Republic of Indonesia number 17 of 2021 and number 16 of 2022.